DETERMINANTS OF HEALTH SEEKING BEHAVIOR AMONG PREGNANT MOTHERS ATTENDING ANTENATAL CARE AT MALANGALA HEALTH CENTER III, MITYANA DISTRICT. A CROSS-SECTIONAL STUDY. - Scovia Nandegeya; Donatus Kimera (Student's Journal of Health Research, 2023)
Background A study was carried out to identify the determinants of health-seeking behaviors among pregnant mothers attending Antenatal Care at Malangala Health Center III, Mityana District.  Methodology: The study was a descriptive cross-sectional and it employed both quantitative and qualitative data collection methods. A sample size of 30 respondents was selected using a convenience sampling procedure. An interview guide was used to collect data.  Results: 20 (67%) did not receive adequate support and encouragement from their husband/partner to ensure access to health care services, 18 (60%) had never been health educated about home treatment for illnesses, 12 (40%) respondents resided 4 - 5 km away from Malangala Health Center III and 12 (40%) respondents spent between 5000 - 10,000shs on transport to the health facility. 20 (67%) reported that health workers had bad behavior towards patients as they were rude and not welcoming, 20 (67%) reported that health workers had negative attitudes during the provision of ANC services to mothers, 10 (33.3%) reported rude and unwelcoming health workers, as well as 8 (26.7%), reported inefficient and slow health staff.  12 (40%) respondents rated the quality of medical care received the last time they used the health care services as very good, 11 (36.7%) spent 30 minutes to 1 hour, 8 (26.7%) spent more than 4 hours, 18 (60%) reported that Malangala Health Center III is not accessible from their homes, 12 (40%) were sometimes able to get all the required services and medication. Conclusion:  Respondents faced various socio-economic, health worker, and health facility determinants of health-seeking behaviors among pregnant mothers attending ANC services.  Recommendations: Including improving efficiency and reducing waiting time, improving customer care, more support, and health education about ANC among others.